Feasibility of a behavioral automaticity intervention among African Americans at risk for metabolic syndrome - Heather Fritz; Wassim Tarraf; Aaron Brody; Philip Levy (BMC, 2019)
Abstract Background Targeting habit-development (behavioral automaticity) as part of healthy lifestyle behavior change interventions may improve the adoption and maintenance of healthful behaviors. Few studies, however, have evaluated the feasibility of using a habit-development approach to foster the adoption of recommended physical activity and dietary behaviors. We report quantitative and qualitative data from a feasibility study evaluating a habit-formation intervention to foster healthy dietary and physical activity habits among middle aged African Americans with metabolic syndrome. Methods Using a non-comparative design we evaluated the feasibility an 8-week, hybrid format (telecoaching and face-to-face sessions), habit-focused intervention targeting the development of healthful dietary and physical activity habit development among 24 African Americans aged 40 and older with metabolic syndrome recruited from the emergency department - a setting where individuals in under-resourced communities often go for primary care. We administered behavioral automaticity measures tailored to participants' self-selected habits biweekly during the intervention and collected clinical outcomes of systolic blood pressure, weight, waist circumference, and BMI at baseline week 20. Results Participant attrition from the program was high (~ 50%). Despite high levels of attrition, 92% of intervention completers were extremely satisfied with the program. Intervention completers also experienced gains in behavioral automaticity for both dietary and physical activity habits. Overall, higher levels of adherence were associated with higher positive gains in automaticity with the statistical significance of the associations being more pronounced for physical activity habit plans relative to dietary habit plans. Conclusions Our preliminary data support a habit-development approach for fostering the adoption of healthful dietary and physical activity habits. However, in this pilot study high rates of attrition were seen, suggesting that strategies to improve retention and participant engagement should be included in future studies, particularly when targeting African American emergency department patients. Trial registration ClinicalTrials.gov ID: NCT03370419 Registered 12/11/2017, retrospectively registered.